PENGARUH BIAYA PROMOSI PENJUALAN TERHADAP VOLUME PENJUALAN PT RIANDA GANDA MANDIRI DI PEKANBARU - Yulia Desmita Yulia Desmita; Suarman '; Ngadlan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research aims to find out how big the influence of sales promotion costs to sales volume. This research was conducted in PT Rianda Ganda Mandiri in Pekanbaru. Located in the way of a rajawali street no.86 F Sukajadi Pekanbaru, appointed by PT. Shell Indonesia Campanies in 1997 as the official distributors. The research was carried out in May-June 2014. The data used is primary data, namely data any information obtained, observed and noted by the researchers directly from the company that became the object of research. A promotional forms were used, obtained from PT Rianda Ganda Mandiri and data secondary the data or information derived from the company, in the form of data on the volume of sales and promotion costs obtained in the sale of PT Rianda Ganda Mandiri. Results of calculation shows tcalculate>ttable (t6.819>t2.032),it means there is a significant influence among the promotional cost of sales volume. And the magnitude of the effect of sales promotioncosts to sales volume PT Rianda Ganda Mandiri in Pekanbaru is equl to 57.8%, while the rest in influenced by other factors not examined this study, as the cost of advertising, publicity fees, the cost of personal selling. Therefore, if the company wants to increase the volume of sales it needs to also increase the cost ofthe sales promotion. Key Words:Cost of Sales Promotion, Sales Volume